PENINGKATAN AKTIVITAS BELAJAR EKONOMI DALAM PEMBELAJARAN COOPERATIVE LEARNING TYPE STUDENT TEAMS ACHIEMENTS DIVISION (STAD) PADA SMPN 14 PADANG (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
This research aims to obtain a picture of how STAD model cooperative learning can enhance students' learning activities in class VII Economic IPS SMP 14 Padang. Type of research is a class act. Which in this study consisted of two cycles and each cycle there are three meetings.These results indicate activity of students in cycle one and two respectively silkus increased. In cycle one of the nine descriptors six of which have exceeded 56% of that increase students' skills in listening, describing, questioning, discussing, responding and concluded while the ability to observe, describe and convey the idea has actually been performing well but has not reached 65%. While in the second cycle of the nine descriptors each is performing well.